Church in Middle of Religious Pluralism: Presenting Environmentally Friendly Christianity - Setinawati; Kawangung, Yudhi; Saputra, Sion (International Journal of Psychosocial Rehabilitation, 2020)
The church lives in a pluralistic world, and the church is amid religious pluralism. Religious pluralism in its journey has become a source of tensions many times and even triggers various wars. This is caused by every religion having its truth claims, thereby forcing this understanding of individuals and even communities. One is right thus assuming others are wrong. Yet in essence, no individual is willing to accept outrightly that the religion s/he has adopted is wrong. Therefore, the church needs to maintain harmony between religious communities. To establish harmony and tolerance between religious communities, an effective way is needed, namely dialogue between religious communities for problems almost between each religious group. So, there is a meeting point or a common thread in warm communication. Perhaps during this time conflicts arise between religious communities that occur due to the interruption of the fabric of correct information between adherents of religion from one party to another, so that negative prejudices arise. The church needs to equip itself so as not to be easily swept away but also to remain open and respect the views of other religions without judging one another.